2012
DOI: 10.1002/acr.21690
|View full text |Cite
|
Sign up to set email alerts
|

Rilonacept (interleukin‐1 trap) for prevention of gout flares during initiation of uric acid–lowering therapy: Results from a phase III randomized, double‐blind, placebo‐controlled, confirmatory efficacy study

Abstract: Objective. To evaluate the efficacy and safety of the interleukin-1 inhibitor rilonacept (interleukin-1 Trap) for gout flare prevention during initiation of uric acid-lowering therapy (ULT). Methods. In total, 241 adult patients with gout, >2 gout flares within the past year, and a serum urate level >7.5 mg/dl were initiated on allopurinol 300 mg daily and randomly allocated in a 1:1:1 ratio to receive 16 once-weekly subcutaneous injections of placebo, rilonacept 80 mg, or rilonacept 160 mg, with a double (loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 45 publications
(44 reference statements)
3
53
1
3
Order By: Relevance
“…Takie możliwości niesie ze sobą zastosowanie ultraBased on the presented interpretation of the course of acute inflammation in gout, it has been suggested that biological therapy directed against IL-1 may prove very useful in treating acute inflammation in gout. The key role of IL-1 in microcrystal-mediated inflammation has been confirmed in clinical studies in which IL-1 inhibitors (anakinra, rilonacept, and canakinumab) were used to effectively suppress the symptoms of acute gout attacks and to prevent attacks in patients starting treatment with uric acid-lowering medication [17].…”
Section: Nowe Metody Diagnostyczne Dnymentioning
confidence: 89%
See 1 more Smart Citation
“…Takie możliwości niesie ze sobą zastosowanie ultraBased on the presented interpretation of the course of acute inflammation in gout, it has been suggested that biological therapy directed against IL-1 may prove very useful in treating acute inflammation in gout. The key role of IL-1 in microcrystal-mediated inflammation has been confirmed in clinical studies in which IL-1 inhibitors (anakinra, rilonacept, and canakinumab) were used to effectively suppress the symptoms of acute gout attacks and to prevent attacks in patients starting treatment with uric acid-lowering medication [17].…”
Section: Nowe Metody Diagnostyczne Dnymentioning
confidence: 89%
“…Kluczowa rola IL-1 w zapaleniu wywołanym mikrokryształami została potwierdzona w badaniach klinicznych, w których używa -no inhibitorów IL-1 (anakinra, rilonacept, canakinumab) w celu skutecznego hamowania objawów w ostrym napadzie dny i w profilaktyce ataków u chorych rozpoczynających leczenie zmniejszające stężenie kwasu mo czowego [17].…”
Section: New Information On the Pathogenesis Of Goutunclassified
“…Conversely, in a randomized, controlled clinical trial using indomethacin as comparator to rilonacept, rilonacept alone or combined with indomethacin was not significantly superior to indomethacin alone [35]. Rilonacept, with a half-life of 9 days, was overall well tolerated in both studies with adverse reactions noted to be predominately injection site reactions [35,36].…”
Section: Canakinumab and Rilonaceptmentioning
confidence: 91%
“…In a large randomized trial, canakinumab (0.50 mg single dose or four 4-weekly doses) was found to be superior in flare prophylaxis when compared with daily colchicine 0.5 mg in the 16-week follow-up period (87). In several trials, another IL-1 trap, rilonacept, markedly reduced the occurrence of gout flares associated with the initiation of urate-lowering therapy (88,89). The majority of patients can describe a triggering factor that initiated a gout flare, including diet (high consumption of meat or fish), alcohol, and diuretic use (23).…”
Section: Flare Prophylaxismentioning
confidence: 99%